Mathematics in times of covid-19: challenges and implications to the teaching and learning process - Sarduy Nápoles, Delia; Montes de Oca Recio, Nancy; Sobrado Cárdenas, Estrella (Transformación, 2024)
Objective: This article aims at promoting critical thinking on mathematics relevance in times of COVID-19, its challenges and implications to make teaching and learning closing to actual events.Methods: The authoress rely mainly on documentary analysis assisted by analytic and synthetic procedures. Results: Arguments to prove the relevance of Mathematics for society are given; its role to understand and transform the surrounding reality, specifically, those related to COVID-19. Likewise, the authoress devises the essential didactic guidelines for teaching Math in present-day context.Conclusions: The instrumental and educative character of mathematic concepts for modern society poses a challenge for teaching and learning to improve the quality of life. This challenge demands teacher’s commitment and awareness of their decisive role in achieving such goals.
Keywords: Mathematics; mathematics instruction; Didactics; COVID-19; teaching methods